Developing An Effective Model In Teaching Reading: What Would Work Best In A Large English Class? - Dinovia Fannil Kher; Yati Aisya Rani (Jurnal Educative: Journal of Educational Studies, 2019)
This article discusses the preliminary process of developing a suitable model for teaching reading in large English classes. The large English classes that are referred in this piece of scientific writing is the English classes at Universitas Negeri Padang which consist up to fifty to sixty students. Not only it is large, but the students in the class also come from various study programs and different cultural background. The diversity of their background of knowledge and culture leads to possible problems regarding their study. The condition requires the lecturer to be able to apply an effective model in the teaching and learning process. The article focuses on the development of a reading model since enriching the students' abilities in reading is one of the objectives of the course. The development process includes the planning of the reading lesson, the learning process, and the evaluation. Various methods of teaching are applied to find the one that works best for the atmosphere of the large classes. However, it was found that none of the common teaching reading strategies used worked well in the large English class at Universitas Negeri Padang. Artikel ini ditulis sebagai hasil penelitian pemula tentang usaha pengembangan model mengajar reading di kelas bahasa Inggris berkapasitas besar. Kelas berkapasitas besar yang dimaksud dalam tulisan ilmiah adalah kelas bahasa Inggris mata kuliah umum di Universitas Negeri Padang yang terdiri dari lima puluh hingga enam puluh mahasiswa. Tidak hanya berkapasitas besar, tetapi mahasiswa dikelas ini berasal dari jurusan yang berbeda-beda. Perbedaan ini menyebabkan terjadinya beberapa masalah terkait proses belajar mengahar dikelas. Kondisi semacam ini mengharuskan dosen untuk mampu mengplikasikan model belajar mengajar yang efektif. Fokus dari tulisan ini adalah dasar pengembangan model mengajar reading yang mampu membantu mahasiswa mencapai tujuan pembelajaran. Pengembangan yang dimaksud mencakup merencanakan pembelajaran, proses pembelajaran termasuk contoh strategi dan teknik yang mungkin dapat digunakan serta evaluasi. Akan tetapi, ditemukan bahwa hampir tidak ada dari satu strategi mengajar reading yang umum digunakan mampu membantu mahasiswa dikelas-kelas berkapasitas besar ini untuk mencapai tujuan pembelajaran yang diharapkan.